Performance simulation and applicability analysis of hybrid air conditioner in cooling season. (15th February 2022) - Yang, Zixu; Xiao, Hansong; Wang, Baolong; Zhang, Youlin; Cui, Mengdi; Huang, Boliang; Zhao, Jiaan; Shi, Wenxing
Abstract: In recent years, it has been observed that room air conditioners require considerable amounts of electricity. In this study, the annual performance and applicability of a hybrid air conditioner combining a fresh air ventilator and direct evaporative cooling water spray system were evaluated. The direct ventilation temperature degree-hour (TDH), evaporative cooling enthalpy degree-hour (IDH), and hybrid temperature degree-hour (TIDH) were defined to represent the applicability of natural energy. Meteorological data in China was used to determine the natural source utilization potential for direct ventilation and evaporative cooling. An applicability analysis was conducted in 334 cities in China. To further analyze the energy-saving potential, a simulation model was established and verified for the hybrid air conditioner based on laboratory tests. The operation periods with different work modes, energy-saving rates, and energy efficiency values were considered for three typical cities, i.e., Nanjing, Beijing, and Lanzhou, representing wet, semi-wet, dry, and semi-dry zones, respectively. Considering the extra energy consumption of the ventilator, the total energy consumption was reduced in these cities by 6.4%, 22.6%, and 50.2%, respectively, and the system seasonal energy efficiency ratios (SEERs) improved by 6.9%, 29.3%, and 98.9%, respectively. Finally, the energy-saving potential, operation ratios, and absolute energy-saving values were calculated and analyzed for 31 provinces in different working zones. The results indicate that the proposed system has the best applicability and energy-saving potential in northern China. Highlights: A simulation model was established for a hybrid air conditioner. An applicability analysis was conducted in 334 Chinese cities. Energy consumption was reduced by 6.4, 22.6, and 50.2% in three typical cities. The energy-saving potential in 31 provinces was calculated and analyzed.